PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PENDEKATAN STRUKTURAL NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN MOTIVASI BELAJAR MATEMATIKA SISWA KELAS VIII.5 SMP NEGERI 25 PEKANBARU - Shari, Andi Kumala; Yuanita, Putri; ', Sakur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is conducted based on the unsatisfied process in learning mathematics at grade VIII.5 of SMP Negeri 25 Pekanbaru. It was seen from the low motivation of the students to learn mathematics whilethe learning process. These problems impact on the number of students who pass KD 4.1 Determine the elements and parts of the circle; 4.2 Counting the circumference of a circle; And 4.3 Using the relationship of center angle, arc length, area of juring in problem solving test with percentage of 47,6%. The research was a Classroom Action Research that aims to improve the learning process and increase the motivation of the students to learn mathematics by implementing Cooperative Learning Approach Structural of Numbered Heads Together (NHT). There were 42 students in the class consisting 21 boys and 21 girls as the participant of this research. The instruments of data collecting in this research were observation sheets (observation of teacher and students activity and observation of students motivation) and the motivation questionnaire. The observation sheets were analyzed in qualitative descriptive, while the motivation questionnaire were analyzed using the Wilcoxon signed-rank test. The qualitative descriptive showed an improvement of learning process and the motivation of students to learn mathematics at grade VIII.5 of SMP Negeri 25 Pekanbaru better after the action than before the action. The Wilcoxon signed-rank test for all indicators of motivation questionnaire obtained Z = -3,858, so that = 0,0001 < α = 0,05 and for each indicator of the motivation to learn mathematics obtained . From this test is rejected, in other words, the motivation to learn mathematics at grade VIII.5 of SMP Negeri 25 Pekanbaru increased after the action. Based on these results it can be concluded that the application of Cooperative Learning Approach Structural of NHT can improved the learning process and increased motivation to learn mathematics at grade VIII.5 of SMP Negeri 25 Pekanbaru on second semester of academic year 2015/2016.Key Words : Motivation to Learn Mathematics, Cooperative Learning ApproachStructural of Think Pair Square, Classroom Action Research2